ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN UMKM SEKTOR KULINER DI KECAMATAN KUTA - Paryatmana, I Nyoman Rio; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 1 (2024): Vol.13.No.1. JANUARI 2024[1-90]DO - 10.24843/EEP.2024.v13.i01.p04, 2024)
MSMEs have a significant role in the economy in Badung Regency. Based on data on the performance of MSMEs in Badung Regency in 2022 MSMEs engaged in the culinary sector have the highest number. Kuta District is one of the sub-districts in Badung Regency with a fairly high increase in MSMEs. The MSME sector that has the highest increase in the number of businesses is the MSME culinary sector. The growth of MSMEs in the Culinary sector in Kuta District over the past three years has the highest number compared to other sectors. The purpose of this study is to evaluate the elements that play a role in influencing the income of SMEs in the culinary sector in the Kuta District area. The data collected originates from primary data sources, and the analytical approach applied is multiple linear regression. The results showed that capital, working hours and e-commerce simultaneously affected the culinary sector MSME income and partially capital and working hours had a positive and significant effect on culinary sector MSME income, while e-commerce was a dummy variable stating that culinary sector MSME income that use e-commerce is higher than culinary sector MSMEs that do not use e-commerce. Keyword : capital, working hours, e-commerce, income